2012
DOI: 10.1080/08111146.2012.660872
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Transport Services: Overcoming Barriers to Implementation in Low-Density Urban Areas

Abstract: Flexible transport services include a range of passenger transport mobility offers, where services are flexible in one or more of the dimensions of route, vehicle allocation, vehicle operator, type of payment and passenger category. Although flexible transport services are used increasingly in Europe and the USA as part of the public transport mix where regular services are not sustainable, there are few working examples of these services in urban Australia, although there are many opportunities. Through a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…The presence of more than one scheme or provision with different modes was also a factor increasing lack of awareness. Other examples include difficulties in understanding the concept of sharing any transport mode apart from buses (e.g., shared taxis) [65], or that FTS operate as conventional taxis due to the availability of booking services [110]. Furthermore, the high level of flexibility offered can lead to identification problems, since the more flexible the service is, the less visible it becomes to potential users.…”
Section: Ftsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of more than one scheme or provision with different modes was also a factor increasing lack of awareness. Other examples include difficulties in understanding the concept of sharing any transport mode apart from buses (e.g., shared taxis) [65], or that FTS operate as conventional taxis due to the availability of booking services [110]. Furthermore, the high level of flexibility offered can lead to identification problems, since the more flexible the service is, the less visible it becomes to potential users.…”
Section: Ftsmentioning
confidence: 99%
“…Ahern and Hine [41] found that community transport in Irish rural areas was recognized as a "feminized" transport mode by male participants and therefore not used to meet their transport needs. While mainstream fixed-route public transport is regarded as normal, FTS can be perceived as a specialized service for impaired or generally disadvantaged people [65,83]. Glasgow and Blakely [18] found that the "young-older" (60-74 years old) reported low consideration of FTS due to the stigma associated with using these transport modes, while Kim [111] found a correlation between modal choice preference and age, with the older cohorts reporting more usage of FTS.…”
Section: Ftsmentioning
confidence: 99%
See 1 more Smart Citation
“…Constraint (9) does the same for the second transfer points. Constraint (10) ensures that if k and l are the first and second transfer points of the selected path from i to j then x kl equals 1. In case both z 1 ijk and z 2 ijl become the constraint will reduce to x kl ≥ 1 and hence x kl must be 1.…”
Section: Formulation Of the Route Selection Problemmentioning
confidence: 99%
“…In many developed countries therefore FTSs are used for feeding the conventional public transport network . Further FTSs are introduced in order to provide suitable services for people with disabilities or to improve social inclusion in low‐density urban areas . In contrast, in developing countries, the underlying motivations to maintain FTSs are different.…”
Section: Introductionmentioning
confidence: 99%